Pathological Localism or Vernacular Glocalization? Populism, Globalism and the Everyday Politics of Anger (Glocalism: Journal of Culture, Politics and Innovation, 2020)
Globality and consciousness of it are reflexively linked, possibly through a modal empathy whereby all humanity has a built-in predisposition for social understanding and cooperation. But in more ardent accounts of world-making, global awareness produces not empathy but identities in conflict, insecurity and woundingly agonistic politics. An intriguing and forceful example of global consciousness having the potential to cut both ways is the current wave of populism: a seemingly localist force that may still produce glocalist outcomes. This essay explores some of the visceral factors that underlie such variability.
Keywords: localism; glocalization; populism; global consciousness; anger